Portfolio Method for Learning ESP in the Context of Paradigm Change - Burkšaitienė, Nijolė (Acta Paedagogica Vilnensia, 2006)
A plethora of research carried out during the last three decades proves that education systems in many countries are facing a fundamental change from the traditional teaching paradigm towards process oriented learning paradigm. In the context of paradigm shift towards lifelong learning higher education has changed. It has become open to the new type of learners; therefore, it has to tailor its curriculum design and teaching methodologies to the requirements of the new learning conditions and the real world of work. The article presents the results of the research aimed at fostering student learning of English for Law through the integration of portfolio method into the course of ESP in the context of paradigm shift at tertiary level. The results of the study prove that portfolio method has had a positive impact to students’ achievements: at the end of the course the learners in the experimental group demonstrated higher results than the learners in the control group. The difference in results was statistically significant. Study results also show that after the experiment student sati